THE INFLUENCE OF PRICE AND LIFESTYLE ON PURCHASING DECISIONS AT NADIFA PAPPING COFFEE START - Matulu, Silfana; Rizal; Youlanda Hasan (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The objectives of this research are 1) To determine and analyze the significant influence of price on purchasing decisions at the Nadifa Paping Coffee Shop, Linawan Village 1, Pinolosian District, South Bolaang Mongondow Regency; 2) To determine and analyze the influence of lifestyle on purchasing decisions at the Nadifa Paping Coffee Shop, Linawan Village 1, Pinolosian District; 3) To determine and analyze the significant influence simultaneously between Price and Lifestyle on Purchasing Decisions at the Nadifa Paping Coffee Shop, Linawan Village 1, Pinolosian District, South Bolaang Mongondow Regency. The method in this research uses an associative quantitative approach with data collection techniques using observation, distributing questionnaires and documentation The results of the research show 1) Testing the t test hypothesis has a significant influence between price on purchasing decisions at the Nadifa Paping Coffee Shop, Linawan Village 1, Pinolosian District. The relationship between price and purchasing decisions has a very close influence, because price is one of the factors that influences someone to make purchasing decisions; 2) testing the hypothesis that there is a significant influence between lifestyle on the decision of Nadifa Paping Coffee Shop, Linawan Village 1, Pinolosian District. The relationship between lifestyle and purchasing decisions will influence a person's consumer patterns, where consumers will choose products that suit their lifestyle; 3) hypothesis that price and lifestyle together have a positive and significant effect on purchasing decisions.